Space Physics: The Need for a Wider Perspective - André, Mats (Frontiers in Astronomy and Space Sciences, 2022)
We argue that many studies in space physics would benefit from putting a detailed investigation into a wider perspective. Three examples of theoretical and observational studies are given. We argue that space physics should aim to be less of an isolated branch of science. Rather, by putting the scientific space results into a wider perspective these results will become more interesting and important than ever. We argue that diversity in a team often is favourable for work on complicated problems and helps to present the results in a wider perspective.